Behavioral and Neurochemical Phenotyping of Mice Incapable of Homer1a Induction - Datko, Michael C.; Hu, Jia-Hua; Williams, Melanie; Reyes, Cindy M.; Lominac, Kevin D.; von Jonquieres, Georg; Klugmann, Matthias; Worley, Paul F.; Szumlinski, Karen K. (Frontiers in Behavioral Neuroscience, 2017)
Immediate early and constitutively expressed products of the Homer1 gene regulate the functional assembly of postsynaptic density proteins at glutamatergic synapses to influence excitatory neurotransmission and synaptic plasticity. Earlier studies of Homer1 gene knock-out (KO) mice indicated active, but distinct, roles for IEG and constitutively expressed Homer1 gene products in regulating cognitive, emotional, motivational and sensorimotor processing, as well as behavioral and neurochemical sensitivity to cocaine. More recent characterization of transgenic mice engineered to prevent generation of the IEG form (a.k.a Homer1a KO) pose a critical role for Homer1a in cocaine-induced behavioral and neurochemical sensitization of relevance to drug addiction and related neuropsychiatric disorders. Here, we extend our characterization of the Homer1a KO mouse and report a modest pro-depressant phenotype, but no deleterious effects of the KO upon spatial learning/memory, prepulse inhibition, or cocaine-induced place-conditioning. As we reported previously, Homer1a KO mice did not develop cocaine-induced behavioral or neurochemical sensitization within the nucleus accumbens; however, virus-mediated Homer1a over-expression within the nucleus accumbens reversed the sensitization phenotype of KO mice. We also report several neurochemical abnormalities within the nucleus accumbens of Homer1a KO mice that include: elevated basal dopamine and reduced basal glutamate content, Group1 mGluR agonist-induced glutamate release and high K+-stimulated release of dopamine and glutamate within this region. Many of the neurochemical anomalies exhibited by Homer1a KO mice are recapitulated upon deletion of the entire Homer1 gene; however, Homer1 deletion did not affect NAC dopamine or alter K+-stimulated neurotransmitter release within this region. These data show that the selective deletion of Homer1a produces a behavioral and neurochemical phenotype that is distinguishable from that produced by deletion of the entire Homer1 gene. Moreover, the data indicate a specific role for Homer1a in regulating cocaine-induced behavioral and neurochemical sensitization of potential relevance to the psychotogenic properties of this drug.